Tolerance and Intolerance on the Border Between Civil and Military Croatia in the 18th Century. Zagreb County and Karlovac Generalate - Holjevac, Željko (2007)
The author deals with problems of (non)existence of tolerance and intolerance on the border between Civil Croatia and Karlovac Generalate during the 18th century, when that border was fixed in official terms.
Projekt MZOS
ENG